Equity, cohesion and social economy - de Castro Sanz, Marcos (Cuadernos de Trabajo Social, 2013)
Economic deregulation has already caused tears in the social fabric threatening our social model. Once it is destroyed, as social cohesion is no longer a main objective of Policies, many people are in process of social exclusion, if not excluded, and neglected, increasing even more the inherited gap, created by an obsessive pursuit of profit. It is unlikely that politics will address these social injuries, consequence of placing the economy above all. Only solidarity flows within our societies will be able to act as a barrier to avoid the collapse of social equity. The engine of these flows is social economy; born out of solidarity can help building social cohesion while creating wealth.